Pemanfaatan Platform YouTube sebagai Sumber Media Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Tarmizi, Tarmizi (Jurnal Ilmiah Guru Madrasah, 2025)
The rapid development of digital technology has significantly influenced the educational landscape, including the teaching of Islamic Religious Education (PAI) at the elementary level. One of the most widely used platforms with great potential for supporting learning activities is YouTube. This study aims to analyze how YouTube can be effectively utilized as a learning resource to enhance students’ interest in Islamic Religious Education. The research employs a library research method by reviewing relevant literature, scientific articles, and digital sources related to the topic. The findings reveal that YouTube’s visual and auditory strength can effectively capture students’ attention, making learning more interactive and meaningful. This platform enables teachers to connect Islamic values with real-life contexts through engaging digital presentations. However, its effectiveness largely depends on the teacher’s ability to select and guide content aligned with the goals of Islamic education. The study concludes that YouTube functions not only as a visual aid but also as a transformative medium that bridges students’ digital world with moderate and humanistic Islamic values. This research contributes conceptually to developing adaptive models of religious education in the digital era and promotes digital literacy among Islamic education teachers.